Essential criminology - Lanier, Mark M. (Westview Press, 2010)
What is criminology? the study of crime, criminals, and victims in a global context -- What is crime? defining the problem -- Classical, neoclassical, and rational choice theories -- "Born to be bad" : biological, physiological, and biosocial theories of crime -- Criminal minds : psychiatric and psychological explanations for crime -- Learning criminal behavior : social process theories -- Failed socialization : control theory, social bonds, and labeling -- Crimes of place : social ecology and cultural theories of crime -- The sick society : anomie, strain, and subcultural theory -- Capitalism as a criminogenic society : conflict and radical theories of crime -- Patriarchy, gender, and crime : feminist criminological theory -- New directions in criminological theory